Chemical composition, antioxidant and allelopathic activities of essential oils and crude extracts of Cupressus arizonica Greene - Dhaouadi, Ferjani; Mouna, Souihi; Ismail, Amri; Fedia, Mejri; Sana, Khedhri; Yassine, Mabrouk; Lamia, Hamrouni; Naceur, Mejri (Phytoprotection, 2022)
Chemical composition, antioxidant, and allelopathic activities of extract from leaves and cones of Tunisian Cupressus arizonica were evaluated. The values of essential oils (EO) yields were 0.18% for leaves and 1.07% for cones. Following GC/MS analysis of C. arizonica leaves and cones, the major compounds identified in leaves EO were umbellulone (19.4%) and α-pinene (10.75%) while the EO of the cones was characterized by its richness with α-pinene (81.3%). In comparison with different extracts, the highest total antioxidant capacity was registered with ethanolic extracts of leaves followed by that of cones. However, the antioxidant activity was stronger with ethanolic extract of leaves than that of cones using both DPPH or ABTS in free radical scavenging activity assays. Results of allelopathic activity showed that the germination reduction depends on the nature of extract and their concentration level. All extracts of C. arizonica decreased the germination of Sinapis arvensis compared to the control. The EO from leaves and cones had the greatest reduction on germination and the strongest growth inhibition followed by the ethanolic extract then the aqueous extract. Results of this study can lead to identification of new phytotoxic compounds in extracts of C. arizonica useful in controlling weeds.